Volcanoes - Simon, Seymour (New York : Collins, 1988)
Explains, in simple terms, the characteristics of volcanoes and describes some famous eruptions and their aftermath.
"Smithsonian.".
Includes index.
5.1
3-6
Keywords: Volcanoes -- Juvenile literature; Volcanoes; Volcanoes